2015
DOI: 10.5194/acp-15-2675-2015
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of small-scale integrated water vapour variability during HOPE

Abstract: Abstract. The spatio-temporal variability of integrated water vapour (IWV) on small scales of less than 10 km and hours is assessed with data from the 2 months of the High Definition Clouds and Precipitation for advancing Climate Prediction (HD(CP) 2 ) Observational Prototype Experiment (HOPE). The statistical intercomparison of the unique set of observations during HOPE (microwave radiometer (MWR), Global Positioning System (GPS), sun photometer, radiosondes, Raman lidar, infrared and near-infrared Moderate R… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
72
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(88 citation statements)
references
References 39 publications
12
72
0
4
Order By: Relevance
“…The values are small in all situations and lie inside the GPS uncertainty of 1-2 kg m −2 (Gendt et al, 2004) and the MWR product of ∼ 0.5-1 kg m −2 (Steinke et al, 2015). While the only-MWR case presents a negative bias of ∼ 0.5 kg m −2 , the inclusion of the RL in the RL+MWR case corrects this bias, reducing it 1 order of magnitude.…”
Section: Integrated Water Vapormentioning
confidence: 88%
See 1 more Smart Citation
“…The values are small in all situations and lie inside the GPS uncertainty of 1-2 kg m −2 (Gendt et al, 2004) and the MWR product of ∼ 0.5-1 kg m −2 (Steinke et al, 2015). While the only-MWR case presents a negative bias of ∼ 0.5 kg m −2 , the inclusion of the RL in the RL+MWR case corrects this bias, reducing it 1 order of magnitude.…”
Section: Integrated Water Vapormentioning
confidence: 88%
“…Note that this flexible framework allows the retrieval of temperature once corresponding RL and MWR data are available. The method was applied to the 2-month dataset collected during HOPE (HD(CP) 2 Observational Prototype Experiment), where a multitude of groundbased remote sensing instruments for the investigation of boundary layer and cloud processes were operated (Steinke et al, 2015;Behrendt et al, 2015;Foth et al, 2015). Here we focus on clear sky cases and absolute humidity profiles.…”
mentioning
confidence: 99%
“…A main characteristic of tropospheric humidity is the high short-term and small-scale variability, which make intercomparison studies difficult. Concerning temporal variability, Steinke et al (2015) reported good correlation of integrated water vapour (IWV) observations and simulations made within 3 h (see their Fig. 7).…”
Section: Data Availabilitymentioning
confidence: 99%
“…Spatial variability can be estimated by spacebased observations or by models. Steinke et al (2015) used ICON simulations and estimated the scatter for humidity encountered at a distance of 10 km to be about 4 % (right column in their Fig. 4 using an IWV of 12 kg m −2 from their Fig.…”
Section: Data Availabilitymentioning
confidence: 99%
“…The DFM-09 radiosonde is a lightweight weather radiosonde that measures temperature (at a resolution of 0.1 • C with an accuracy of 0.2 • C), pressure (at a resolution of 0.1 hPa with an accuracy of 0.5 hPa), RH (at a resolution of 1 % with an accuracy of 2 %), and wind speed (accuracy = 0.2 m s −1 ) (Navas-Guzmán et al, 2014). RH is measured by a thin-film capacitance sensor, and its uncertainties and errors depend on temperature and GPS location (Steinke et al, 2015). Data acquisition and processing were performed at the Graw ground station located at the Xingtai supersite using the Grawmet software.…”
Section: Radiosondesmentioning
confidence: 99%